Distribution of minor histocompatibility antigens HA-1, HA-2 and HA-8 in the Croatian population - Posavec, Ana (Array, 2020)
Minor histocompatibility antigens (mHAgs) are polymorphic, endogenously synthetized products recognized by alloreactive T cells in the context of major histocompatibility complex molecules. Recipients of allogeneic bone marrow grafts run the risk of graft-versus-host disease (GvHD), even when the donor is an HLA-identical sibling. This may be caused by disparities in mHAgs between the donor and the recipient, with the antigen present in the recipient and not in the donor. In such cases, T cells in the transplanted donor marrow respond to the recipient’s mHAgs. We determined the allele, genotype and phenotype frequencies for mHAgs HA-1, HA-2 and HA-8 in 102 healthy, unrelated individuals previously typed for HLA-A, HLA-B and HLA-DR. We compared the results with existing studies in other populations and found no significant differences between allele, genotype and phenotype frequencies in the Croatian population and frequencies reported for Caucasian population. The results presented will be used for further studies investigating the role of mHAgs in hematopoietic stem cell transplantation.